Tentacle : a graph-based database system - Welz, Gerhard Marc (Department of Computer Science, 2023)
With the advent of large and complex applications and the emergence of semi-structured information repositories such as the World Wide Web, new demands are being made on database systems. The TENTACLE database system is an experimental database system which provides facilities capable of meeting some of these demands. The distinguishing features of the system are that it: uses a graph-based data model (and storage subsystem) to provide a flexible means of representing poorly structured information, integrates a path expression-based query language with a general purpose language to query and manipulate the graph structures, thereby eliminating the impedance mismatch encountered in a two language system, and provides a programmable database kernel capable of executing the combined query and utility language, allowing the construction of domain specific applications inside the database without the assistance of wrappers or gateways. As a demonstration of the utility of the system, I have constructed a hypertext server inside the TENTACLE database without making use of external mediators or gateways. Since the hypertext server program is part of the database content, database facilities may be used to assist in the creation and maintenance of the hypertext server itself. In addition, the close integration of hypertext server and database simplifies tasks such as the management of associations between hypertext entities or the maintenance of different document views.